Investigation on the effect of multi filler loading in graphite-polypropylene composite as bipolar plate - Md Yusuf, Muhammad Yusri (UTeM, 2018)
Materials used to fabricate the bipolar plates for Polymer Electrolyte Membrane Fuel Cell (PEMFC) need to have a good set of criteria such as light, strong, low-cost, easily fabricated, mechanically stable, and have low surface contact resistance. Additionally, PEMFC‟s performance is much influenced by the materials used, type of flow channel design and shape to be fabricated on the bipolar plate surface. In this study, the fabrication of flow channel through hot compression molding method is developed. All materials used were in powder form, which are Graphite (G), Carbon black (CB) and Ferum (Fe) as fillers and the Polypropylene (PP) that acts as binder. The ratio of fillers (G/CB/Fe) and binder (PP) was fixed at 80:20. The fillers ratio was fixed in the range of (25 up to 65 wt%) G, (10 up to 30 wt%) CB and (5 up to 25 wt%) Fe and all fillers were mixed by using the ball mill machine. The second stage of mixing process is between the mixer of fillers and binder, which was mixed by using internal mixer machine. Subsequently, the compaction process through hot compression molding is done to produce G/CB/Fe/PP composite. Then, the inplane electrical conductivity and mechanical properties such as flexure strength, bulk density and shore hardness is measure. Based on electrical conductivity, flexure strength, bulk density and shore hardness, sample with 15 wt% of Fe, has shown as the best result that is 137.39 S/cm3, 34.04 MPa, 1.582 g/cm3, 53.14 respectively. During hot compression molding process, at the same time the flow channel of serpentine type, cooling channel and the shapes of U or V shapes is pressed on the surface of the sample of bipolar plate. Thus, flow channel was investigated for accuracy of surface condition of flow channel dimensions (used coordinate measurement machine) and subsequently, compared with the actual drawings and it‟s process ability. Meanwhile based on the analysis of flow channel dimensions (width, depth, rib, angle draft), the V shape is shown to give a smooth surface, with the dimensions difference between samples and drawing of about 0.118 up to 0.27%. While for the process ability, the V shape is much easier to release from the mold. As a summary, this study revealed that the flow channel dimensions (width, depth, rib, angle draft) and coling channel with V shape can be fabricated through hot compression molding method with high accuracy.